The Most Important Reason to Educate Students with Knowledge to Measure Refractive Index: Evaluated From The Impact On Judd-Ofelt Analysis of Tellurite Based Glass - Adi Pramuda; Ahmad Marzuki; C Cari; Soka Hadiati (Universitas Sebelas Maret, 2016)
This study presents an overview influence of the refractive index parameter to the parameter and radiative properties of analyticaly results on Judd Ofelt tellurite based glass, in the hope of clarifying the importance of education with good refractive index measurement. The main stages carried out is the matching between the result of the parameters and the radiative properties of analytical results on Judd Ofelt tellurite glass with composition 55TeO2-2Bi2O3-(40-x) ZnO-3NA2O-xNd2O3 (x = 2.5) from a value the refractive index is estimated by the value of the refractive index obtained by measurement using Brewster angle method. The results showed that the difference in the Brewster angle ranging from 2o course, will change the value of laser parameters and radiative properties Judd-Ofelt analytical results, with the exception of the Branching Ratio value. Still very much needed insight for learners to use this method. This is an example of a case where educators need to create activities that will facilitate learning well to push the conceptual change. Experiment with new variation of activities will encourage a conceptual change and the ability to analogize concept.Keywords: Refractive Index, Judd-Ofelt, Tellurite, Glass